HIGHER EDUCATION MANAGEMENT INFORMATION SYSTEM (STUDY AT STATE ISLAMIC INSTITUTE CURUP INDONESIA) - Sumarto, Sumarto; Kholilah Harahap, Emmi (Corolla International Conference, 2022)
Management information systems are needed by every educational institution, especially higher education. This paper uses a research methodology with a descriptive qualitative approach, data collection techniques with interviews, observations and documentation. Data validity by data triangulation. The result of this paper is that the education and teaching process at the Curup State Islamic Institute can take place well if there is an information system, starting when the new student admissions process, filling out study plan cards for one semester, until later when students have completed their studies, everything must be recorded. well in the information system built by universities, such as in the author's college, the information system has been well built. Like the academic portal for lecturers and students, we can do attendance online, upload learning materials that will be taught to students, then students can read the material anywhere and anytime so that it is more effective and efficient, as lecturers we can also monitor the progress of the classes we teach properly, from the first meeting to the last meeting. Likewise, research activities and publications by lecturers and students are well recorded through the Online Journal System, IAIN Curup Repository and the Open Book System managed by the Scientific Publication Center. Until community service activities.